Education in North Borneo: An overview - Mohd. Zaki Ishak (Penerbit UMS, 2019)
This introductory Volume 1 presents six articles related to research in education, in particular North Borneo from the three countries: Malaysia, Indonesia and Brunei Darussalam. It is essential that the focus of research in education is to improve practice in the teaching and learning (Mohd. Zaki, 2009) in any curriculum. The practice is not only, about content knowledge, but also, issues related to pedagogy, psychology, sociology, and assessment. Other than practice, Millar (2003) emphasizes the importance of insights that a teacher can see the familiar in a new way, by sharpening thinking, by directing attention to important issues, by clarifying problems, challenging established views, encouraging debate and stimulating curiosity. The focus, practice and insights, are reflected in these six articles.